Experimental Investigation on Solar–Thermal Conversion and Migration Characteristics of Nanofluids - Haoyang Sun; Guiping Lin; Haichuan Jin; Ying Zhou; Kuiyuan Ma (Energies, 2022)
Solar–thermal conversion and migration characteristics of nanofluids have attracted intensive attention recently. Due to the strong absorption of solar energy, solar collectors with nanofluids have wide applications in many areas including desalination and power generation. Researchers have mainly focused on the macroscopic performance of nanofluids in solar collectors, but the nanoparticles’ migration characteristics with vapor during phase transformation have not been further investigated. Therefore, an experimental investigation on solar–thermal conversion characteristics of nanofluids and migration characteristics with vapor during phase transformation was conducted in this work, in order to verify the enhancement effect of nanoparticles on solar energy absorption and explore the nanoparticles’ migration behavior with vapor. It was found that part of Ag nanoparticles migrate out of the nanofluids with generated vapor by boiling nanofluids, and most of the nanoparticles remained in the nanofluids. In addition, more Ag nanoparticles migrated with vapor with the increased heating power. The concentration of migrated nanofluids was 20.58 ppm with a power of 16.2 W and 31.39 ppm with a power of 20 W. The investigation pointed out the potential danger of nanofluids in the process of utility and provided a reference for the standardized application of nanofluids.